2021
DOI: 10.3389/fonc.2021.684733
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Dual Checkpoint Inhibition in Advanced Metastatic Osteosarcoma Results in Remission of All Tumor Manifestations—A Report of a Stunning Success in a 37-Year-Old Patient

Abstract: BackgroundPatients with unresectable metastasized osteosarcoma have a poor prognosis. Current treatment options do not offer a chance to cure the disease in this situation. Despite the fact that immunotherapy has expanded its indications continuously over previous years, its use is not yet established in osteosarcoma. There is a lack of randomized controlled studies that could show a significant benefit in this rare tumor entity. So far, efficacy of immunotherapy is only reported in individual cases as well as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The use of ICIs as a last-chance treatment in our patients with other advanced cancers (Table 4) was usually supported by single case reports or studies on small groups of patients in which this type of treatment proved effective [23][24][25][26][27][28][29][30][31][32][33]. We acknowledge several limitations in our study, including the retrospective nature of the study, the diversity of the types of diseases, and the age of the patients in the cohort group.…”
Section: Discussionmentioning
confidence: 82%
“…The use of ICIs as a last-chance treatment in our patients with other advanced cancers (Table 4) was usually supported by single case reports or studies on small groups of patients in which this type of treatment proved effective [23][24][25][26][27][28][29][30][31][32][33]. We acknowledge several limitations in our study, including the retrospective nature of the study, the diversity of the types of diseases, and the age of the patients in the cohort group.…”
Section: Discussionmentioning
confidence: 82%
“…However, in most of these trials, the drugs used showed little to no improvement in prognosis or the therapeutic effect was not observed [ 8 ]. There is, however, documented success in one instance of advanced metastatic osteosarcoma with nivolumab [ 9 ]. Chimeric antigen receptor T-cell (CAR-T) therapy has shown great promise in treating leukemias and lymphomas and may be a viable option for osteosarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of nivolumab and ipilimumab failed to show efficacy in patients with osteosarcoma [46], and a combination of durvalumab (anti-PD-1) and tremelimumab (anti-CTLA4) resulted in two partial responses out of five osteosarcoma patients treated [47]. Several cases reported that the combination of anti-CTLA4 and anti-PD-1 antibodies induced remission and tumor stabilization in patients with metastatic osteosarcoma [48,49], while the addition of camrelizumab (anti-PD-1 inhibitor) to the inhibition of vascular endothelial growth factor receptor 2 (VEGFR2)] using apatinib (tyrosine kinase inhibitor (TKI)) was shown to prolong PFS of patients with advanced osteosarcoma compared with apatinib alone [50]. The overall findings suggest that a combination strategy rather than a stand-alone therapy may be the path to the future.…”
Section: Immune Checkpoint Inhibitors For Osteosarcomamentioning
confidence: 99%